2018
DOI: 10.5539/jas.v10n6p372
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and Boron Application on Growth, Yield, and Quality of Soybean Seeds (Glycine max [L.] Merril)

Abstract: The increased of growth, yield and quality of soybean seeds are expected to occur by applyingP (phosphorus) and B (boron). This research was to investigate the effect of P and application of B their response on growth, yield and quality of soybean seeds. This research was conducted at fieldland and the Laboratory of Seeds and Plant Breeding, Faculty of Agriculture, University of Lampung from November 2016 to April 2017. This treatment was arranged in a 6 × 2 factorial consisting of six doses of P 2 O 5 (0; 50;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The increase growth of plant and number of leaf affects the light received by the plant so that it can improve the performance of photosynthesis and produce many photosynthatase in forms of starch, lipids, and proteins. Photosynthatase is translocated inside the plant which helps to increase the dry matter of the plant [20].…”
Section: Plant Dry Matter Productionmentioning
confidence: 99%
“…The increase growth of plant and number of leaf affects the light received by the plant so that it can improve the performance of photosynthesis and produce many photosynthatase in forms of starch, lipids, and proteins. Photosynthatase is translocated inside the plant which helps to increase the dry matter of the plant [20].…”
Section: Plant Dry Matter Productionmentioning
confidence: 99%
“…He reported that increasing phosphorus levels increased 100-seeds weight. Timotiwu et al (2018) reported that fertilization of P 2 O 5 with dose of 0 kg/ha, weight of 100 grain produced was 11.27 g and increased as 0.005 g of every additional 1 kg of P 2 O 5 . This is in parallel with research of Thoyyibah et al (2014) who stated that application of various doses of phosphate fertilizers in two soybean varieties had significant effect on grain weight per plant, Detam-1 variety which was cultivated 200 kg/ha of phosphate fertilizers produced the highest weight 42.02 g,…”
Section: Seed Yield (Q Ha -1 )mentioning
confidence: 99%
“…This finding is in agreement withEl-Habbasha et al (2005). He reported that increasing phosphorus levels increased 100-seeds weight Timotiwu et al (2018). reported that fertilization of P 2 O 5 with dose of 0 kg/ha, weight of 100 grain produced was 11.27 g and increased as 0.005 g of every additional 1 kg of P 2 O 5 .…”
mentioning
confidence: 99%